A Work study on RC Masterpiece Crafts and Decor, Inc. - Aureada, Crisencia (College of Engineering, 1996)
The system understudy is RC Masterpiece Crafts and Decors, Inc., which manufactures and exports christmas decor and novelty items. The document includes analysis of the methods of doing work. This part includes proposed layout and working conditions. Another part of this paper is the time study where standard time for different jobs were computed along with the capacity of work to perform an operation. The last part is the systems study and procedures analysis. Included are proposed organizational chart and job descriptions and forms analysis.